PENERAPAN PRIVATE CLOUD STORAGE DENGAN MENGGUNAKAN OWNCLOUD DI PT. SUMBERMULIA HASILGUNA (IT GALERI) - Dede Yusup; Suryaningrat (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
Cloud Computing technology with Private Cloud Storage services is and is an answer to problems that often occur in our daily lives, namely the problem of using physical storage devices such as memory cards, flash drives and hard disks where the data contained in them often suffers damage such as physical damage. devices, affected by bad sectors, affected by viruses, lost devices and so on, as often happens to Gallery IT employees who do not re-store or backup their data on storage media. The implementation of private cloud storage using the owncloud application is a solution so that high storage space requirements can be met, the quota given can be unlimited or you can also set the quota for each user. Ease of access because it uses a LAN (local area network) network so it is more secure and flexible for employees to store and access data in owncloud.